2011
DOI: 10.1590/s1807-59322011000500021
|View full text |Cite
|
Sign up to set email alerts
|

An orally active formulation of angiotensin-(1-7) produces an antithrombotic effect

Abstract: INTRODUCTION AND OBJECTIVE:The heptapeptide angiotensin-(1-7) is a component of the renin-angiotensin system, which promotes many beneficial cardiovascular effects, including antithrombotic activity. We have recently shown that the antithrombotic effect of angiotensin-(1-7) involves receptor Mas-mediated NO-release from platelets. Here, we describe an orally active formulation based on angiotensin-(1-7) inclusion in cyclodextrin [Ang-(1-7)- CyD] as an antithrombotic agent. Cyclodextrins are pharmaceutical tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
81
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 24 publications
(47 reference statements)
3
81
0
1
Order By: Relevance
“…Ang-(1-7) is recognized to have an antithrombotic effect. 12,19,27,28 Ang-(1-7) mediates its effect through Mas. 11 Our previous studies reported no increase in renal Mas but a 1.62-fold increase in liver Mas in Bdkrb2 2/2 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Ang-(1-7) is recognized to have an antithrombotic effect. 12,19,27,28 Ang-(1-7) mediates its effect through Mas. 11 Our previous studies reported no increase in renal Mas but a 1.62-fold increase in liver Mas in Bdkrb2 2/2 mice.…”
Section: Discussionmentioning
confidence: 99%
“…This novel compound was denominated [hydroxypropylβ-cyclodextrin/Ang-(1-7) -HPβCD/Ang-(1-7)] (20). It has been described that Ang-(1-7) incorporated into this hydroxypropylβ-cyclodextrin (HPβCD) cavity, can be protected during the passage through the gastrointestinal tract after oral administration (21). A pharmacokinetic test was conducted in rats to estimate the bioavailability of the heptapeptide in the circulation after oral administration of aqueous solution.…”
Section: Supplemental Introductionmentioning
confidence: 99%
“…This novel compound was denominated hydroxypropylβ-cyclodextrin [HPβCD]/Ang-(1-7). [20][21][22] A pharmacokinetic test was conducted in rats to estimate the bioavailability of the compound, showing that oral formulation significantly increased plasma levels of Ang-(1-7) 12-fold over baseline with the observation for 6 hours after its administration 22 (detailed Material is available in the online-only Data Supplement).Importantly, the potential mechanism underlying the fat hepatoprotective effects of Ang-(1-7) included in HPβCD/ Ang-(1-7) in vivo still remains unclear. Thus, the purpose of this study is to evaluate the effect of oral administration of Ang-(1-7) on hepatic functions and on the expression of liver inflammatory markers in mice consuming a HFD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…But its clinical use is limited because of short half-life in vivo. Cyclized Ang-(1-7) (thioether-bridged Ang- (1-7)) and angiotensin-(1-7) inclusion in cyclodextrin (Ang-(1-7)-CyD) exhibited better pharmacokinetic profile in vivo but in experimental models [79,80]. A synthetic analog of Ang-(1-7) TXA127 is in clinical trial for the treatment of PAH.…”
Section: Ace2/ang-(1-7)/mas Axismentioning
confidence: 99%